Use of labetalol and glyceryl trinitrate for induced hypotension in spine surgery- A comparative study - Yeasmeen, Sabina; Siddique, Md Rafayet Ullah; Islam, Amirul; Aktaruzzaman, AKM; Banik, Debabrata; Hye, Abdul (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Induced hypotension is used to reduce blood loss especially in those operations where even a small amount of blood can obscure the operative field such as spine surgery. Objectives: To compare the effect of labetalol with that of glyceryl trinitrate to reduce intraoperative blood loss by inducing elective hypotension without any tachycardia and to improve quality of surgical field during spine surgery. Method: A total number of thirty patients (ASA grade I & II) were selected randomly into two groups, fifteen in each group. Group-I received glyceryl tinitrate (1000?g) and Group-II received labetalol (5mg) intravenously 3 minutes before induction of anaesthesia. Heart rate, mean arterial pressure was observed in two study groups 15 minutes interval in intra-operative period and quality of surgical field was detected by 4 points VRS (Verbal rating scale) after completion of surgery by asking the surgeon. Results: Heart rate varied significantly in two study groups after induction of anaesthesia except baseline and pre induction (p< 0.05). Labetalol associated with improved quality of surgical field visualization than glyceryltrinitrate (p = 0.034). Conclusion: Our study concluded that labetalol is effective than glyceryltrinitrate to reduce blood loss in spine surgery. DOI: http://dx.doi.org/10.3329/jbsa.v22i2.18141 Journal of BSA, 2009; 22(2): 48-53